Soil quality and grain yield as a function of crop rotation in long-term - Tanaka, Katiuça Sueko [UNESP] (2019)
Soil is a non-renewable resource that play a fundamental role on environmental quality and to human well-being. Unsuitable land use and management practices trigger a decline in soil quality, which can lead to soil degradation and lose the capability to grow plants. A strategy to minimize soil degradation is to adopt conservation soil management, such as no-till system. However, the lack of sufficient residues to cover soil surface are compromising the success of no-till system in tropical regions. Furthermore, low precipitation during the autumn/winter season in the Brazilian Cerrado, may affect performance of crops and cover crops during the off-season, and leading to bare fallow periods. Therefore, long-term studies on how cropping systems influence soil quality properties are needed to design the most suitable strategies for more sustainable crop production in the Brazilian Cerrado. An experiment was established in October 2006 on a clayey Rhodic Hapludox soil in Botucatu, São Paulo, Brazil, to investigate choice of winter dry-season management on environmental quality under no-tillage. Cropping systems were with different species cropped during the winter season each year of the summer crop from 2007 to 2017 (fallow, second crop, cover crop, and forage crop). In the first chapter, our objective was to investigate the effects of cropping systems on soil structure and soil biochemical properties. In the second chapter, our objective was to determine how the choice of winter crop/cover crop impacts soil physical properties. And in the last chapter, we aimed to evaluate the effects of cropping systems on soil fertility. The inclusion of forage and cover crops during the winter season has been shown favorable to not only avoid bare fallow periods, but also enhance soil quality and grain yield of the summer crops.